2022
DOI: 10.1186/s13046-022-02284-7
|View full text |Cite
|
Sign up to set email alerts
|

SKP2 drives the sensitivity to neddylation inhibitors and cisplatin in malignant pleural mesothelioma

Abstract: Background The combination of pemetrexed and cisplatin remains the reference first-line systemic therapy for malignant pleural mesothelioma (MPM). Its activity is moderate because of tumor aggressiveness, immune-suppressive environment and resistance to chemotherapy-induced immunogenic cell death (ICD). Preliminary and limited findings suggest that MPM cells have deregulated ubiquitination and proteasome activities, although proteasome inhibitors achieved disappointing clinical results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…It suggested that high SKP2 expression may increase the responsiveness towards MLN4924 in multiple cancer types. This was consistent with the reports that Skp2 drives the sensitivity to MLN4924 in malignant pleural mesothelioma ( Salaroglio et al, 2022 ) and the sensitivity of RB cells to MLN4924 matches their dependency on Skp2 ( Aubry et al, 2020 ). What’s more, it was reported that MLN4924 could inhibit the ubiquitination of Lats1 and 2 mediated by CRL4 DCAF1 , thereby inducing the phosphorylation and inactivation of YAP which led to the inhibition of proliferation in malignant pleural mesothelioma ( Cooper et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…It suggested that high SKP2 expression may increase the responsiveness towards MLN4924 in multiple cancer types. This was consistent with the reports that Skp2 drives the sensitivity to MLN4924 in malignant pleural mesothelioma ( Salaroglio et al, 2022 ) and the sensitivity of RB cells to MLN4924 matches their dependency on Skp2 ( Aubry et al, 2020 ). What’s more, it was reported that MLN4924 could inhibit the ubiquitination of Lats1 and 2 mediated by CRL4 DCAF1 , thereby inducing the phosphorylation and inactivation of YAP which led to the inhibition of proliferation in malignant pleural mesothelioma ( Cooper et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, developing novel neddylation inhibitor agents with improved anticancer efficacy, selectivity, and safety could be a potential future direction for cancer treatment. In addition, an increasing line of evidence suggests that MLN4924 coupled with different anticancer drugs can overcome drug resistance and improve anticancer results [103][104][105][106]. Hence, combined pharmacotherapy or multi-target drugs seem to be promising therapeutic approaches for the future.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…MLN4924 has shown anticancer effects in preclinical adult and pediatric tumor models 17,[51][52][53][54] and good tolerability in Phase I clinical trials as monotherapy and in combination studies in adult cancer patients 40,[55][56][57][58]. Two Phase I studies are ongoing using this agent in combinatorial approaches also in the pediatric cancer setting involving patients with leukemia/lymphoma (NCT03349281, NCT03813147).…”
Section: Discussionmentioning
confidence: 99%